2004
DOI: 10.1037/0278-6133.23.4.388
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Sensitivity to Health Communications: Consideration of Future Consequences.

Abstract: There are reliable individual differences in the extent to which people consider the long- and short-term consequences of their behaviors. Such differences, assessed by the Consideration of Future Consequences (CFC) Scale (A. Strathman, F. Gleicher, D. S. Boninger, & C. S. Edwards, 1994), are hypothesized to influence the impact of a persuasive communication. In an experimental study, the time frame of occurrence of positive and negative consequences of engaging in a new colorectal cancer-screening program was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 49 publications
10
128
1
2
Order By: Relevance
“…These findings are consistent with accumulating evidence that tailoring messages to dispositional characteristics of the message recipient enhances message persuasiveness (Cesario et al, 2004) and leads to behavior change (Latimer et al, 2005(Latimer et al, , 2007Mann et al, 2004;Orbell, Perugini, & Rakow, 2004;Updegraff et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with accumulating evidence that tailoring messages to dispositional characteristics of the message recipient enhances message persuasiveness (Cesario et al, 2004) and leads to behavior change (Latimer et al, 2005(Latimer et al, , 2007Mann et al, 2004;Orbell, Perugini, & Rakow, 2004;Updegraff et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Orbell, Perugini and Rakow (2004) showed that people low in CFC, who generally might perceive preventive health behaviours as risky or costly, may be more persuaded by messages that take care to emphasize the short term positive benefits of action.…”
Section: Discussionmentioning
confidence: 99%
“…One other possibility for intervention is to tailor cessation messages to individuals' time preference. Preliminary analyses in the context of disease screening have found that messages related to the costs and benefits of screening that are tailored to recipients' time perspective lead to greater reported intention to attend for screening than generic messages [18,19].…”
mentioning
confidence: 99%